'For "feather" read "father"': Death and Possibility in Paul Muldoon's Paternal Elegies. Issue 2 (November 2021) - Pietrzak, Wit
Abstract : Focused on Muldoon's father elegies written between his debut collection New Weather and Hay, the present essay argues that these poems evoke paternal death as the founding moment of poetic expression. Only when the father figure has passed away is the space for poetic expression implicitly made available to the son, so that the elegies from 'The Waking Father' all the way to 'The Bangle (Slight Return)' seek to reimagine the father figure as a poetic construct open to reinterpretation beyond the confines of his factual existence. In effect, the poem, as a locus of unconstrained revision of the self, becomes a consoling act that works only insofar as the poem manages to elude closure.